STRATEGI MANAJEMEN SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH DASAR KRISTEN TUNAS DAUD SEJAHTERA CAKRANEGARA NUSA TENGGARA BARAT - I Nyoman Wijana (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
This study aims to explore, analyze, and describe school management which includesthe implementation of school management functions, strategies in implementing vision andmission, improving quality, and innovation. The study was conducted at Tunas Daud SejahteraMataram Elementary School, using a qualitative method. The results of this study indicate that,the application of management functions in the management of Tunas Daud Sejahtera ChristianSchool is coordinated by the foundation by involving all components of the school. The strategiesused by school management to achieve the stated vision and mission are several things, including;Building a pleasant heavenly atmosphere (build a home), Designing Schools as: House ofAdoption: declaring God's Father's love for everyone, House of Learning: preparing everyonefor a life-long learner - learning obedience and norms (what the king likes ), House of Royalty:training the power they have, House of Authority: preparing learners to become kings / queens/ rulers in using their power and possessions. Designing a school as a Center of excellent: doingbest education practices. To support the improvement of school quality, management alsoaccommodates various innovations. Innovation in information technology, budding David Camp,and the Rise Student Comparison program. This study recommends that managers of educationalinstitutions such as schools, in an effort to improve school quality, need to pay attention to allaspects of the school organization.Keywords: Analysis, School Management, Education Quality